The hyperinflammatory spectrum: from defects in cytotoxicity to cytokine control - Planas, Raquel; Felber, Matthias; Vavassori, Stefano; Pachlopnik Schmid, Jana (Frontiers in Immunology, 2023)
Cytotoxic lymphocytes kill target cells through polarized release of the content of cytotoxic granules towards the target cell. The importance of this cytotoxic pathway in immune regulation is evidenced by the severe and often fatal condition, known as hemophagocytic lymphohistiocytosis (HLH) that occurs in mice and humans with inborn errors of lymphocyte cytotoxic function. The clinical and preclinical data indicate that the damage seen in severe, virally triggered HLH is due to an overwhelming immune system reaction and not the direct effects of the virus per se. The main HLH-disease mechanism, which links impaired cytotoxicity to excessive release of pro-inflammatory cytokines is a prolongation of the synapse time between the cytotoxic effector cell and the target cell, which prompts the former to secrete larger amounts of cytokines (including interferon gamma) that activate macrophages. We and others have identified novel genetic HLH spectrum disorders. In the present update, we position these newly reported molecular causes, including CD48-haploinsufficiency and ZNFX1-deficiency, within the pathogenic pathways that lead to HLH. These genetic defects have consequences on the cellular level on a gradient model ranging from impaired lymphocyte cytotoxicity to intrinsic activation of macrophages and virally infected cells. Altogether, it is clear that target cells and macrophages may play an independent role and are not passive bystanders in the pathogenesis of HLH. Understanding these processes which lead to immune dysregulation may pave the way to novel ideas for medical intervention in HLH and virally triggered hypercytokinemia.